2006
DOI: 10.1038/sj.ki.5001517
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ceramide–redox signaling pathway blocks glomerular injury in hyperhomocysteinemic rats

Abstract: Ceramide-activated NAD(P)H oxidase has been reported to participate in homocysteine (Hcys)-induced abnormal metabolism of the extracellular matrix (ECM) in rat glomerular mesangial cells. However, it remains unknown whether this ceramide-redox signaling pathway contributes to glomerular injury induced by hyperhomocysteinemia (hHcys) in vivo. The present study was designed to address this question, defining the role of ceramide and activated NAD(P)H oxidase in the development of hHcys-induced glomerular injury.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 41 publications
2
105
0
Order By: Relevance
“…It was a direct consequence of stimulation of ceramide synthase. In a more recent study, Yi et al also showed that blocking the de novo synthesis of ceramide with myriocin significantly reduced homocysteine-induced ceramide production and glomerular injury in rats [47]. These studies demonstrate that the detrimental effects of homocysteine on many organ systems are mediated by ceramide signaling.…”
Section: Homocysteine and Ceramidementioning
confidence: 85%
“…It was a direct consequence of stimulation of ceramide synthase. In a more recent study, Yi et al also showed that blocking the de novo synthesis of ceramide with myriocin significantly reduced homocysteine-induced ceramide production and glomerular injury in rats [47]. These studies demonstrate that the detrimental effects of homocysteine on many organ systems are mediated by ceramide signaling.…”
Section: Homocysteine and Ceramidementioning
confidence: 85%
“…We further explored the molecular mechanisms mediating the production of these novel effects of Nlrp3 inflammasome in ECs. The production of ROS was shown to be one of the major early factors mediating death factor-induced endothelial injury (5,6,40,49,50). NADPH oxidase-derived ROS associated with ceramide-enriched membrane raft clustering (21,47,52) were found to primarily contribute to the death factor or adipokine visfatin-mediated endothelial dysfunction (13,17,46,48,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…High Hcy has been reported to produce a sustained and abnormal elevation of glomerular arterial wall stress through generation of ROS (57,58). This stress initiates a complex and progressive glomerular remodeling, including activation of MMPs, collagen degradation, glomerular hypertrophy, and dysfunction (22,37).…”
Section: K Wt 2k Wtmentioning
confidence: 99%